Hubungan Ilmu Tasawuf dan Ilmu Kalam Dalam Perspektif Abu-Hamid Muhammad (Al-Ghazali) - Rahmat Lutfi Guefara (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
In the perspective of Abu Hamid Muhammad Al-Ghazali, the relationship between Sufism (Tasawuf) and Islamic theology (Kalam) plays a crucial role in understanding and practicing Islam. Kalam provides an intellectual foundation for conceptual understanding of religious principles, while Sufism offers a profound approach to spirituality and personal experience. According to Al-Ghazali, the integration of these two fields enables individuals to achieve a comprehensive understanding of Islam, encompassing both intellectual and spiritual aspects. By deepening this understanding, a Muslim can draw closer to God and attain true happiness in both this world and the hereafter.